Storie ‘vere’ ed eroine dei romanzi. Rappresentare la Somalia in 'Ilaria Alpi. La ragazza che voleva raccontare l’inferno' e 'Non dirmi che hai paura' - Brioni, Simone (Incontri. Rivista europea di studi italiani, 2016)
‘True’ Stories and Heroines in Novels: The Representation of Somalia in Ilaria Alpi: The Young Woman Who Wanted to Narrate Hell and Don’t Tell Me You Are AfraidThis article analyses Gigliola Alvisi’s Ilaria Alpi: La ragazza che voleva raccontare l’inferno [Ilaria Alpi: The Young Woman Who Wanted to Narrate the Hell] (2014) and Giuseppe Catozzella’s Non dirmi che hai paura [Don’t Tell Me You Are Afraid] (2014), two novels that deal with two recent events in Somali and Italian history, the killing of the journalist Ilaria Alpi in Mogadishu in 1994 and the death of Samia Yosuf Omar while she was trying to reach the Italian shores from Libya by boat. Alvisi’s text is analysed in comparison with other fictional and journalistic representations of Ilaria Alpi, while Non dirmi che hai paura is examined through what Catozzella considers the two constitutive dimensions of the novel: documentation and identification. Drawing on Stefano Jossa’s reflections on the construction of literary heroes, the article challenges Alvisi’s and Catozzella’s claims that they represent ‘true stories’. The article also argues that the main characters of these literary works are portrayed as heroines and role models for the emancipation of Muslim women.